Perceptions regarding the clinical accompaniment of student nurses in the Limpopo Province - Esther M Lekhuleni; Dirk M van der Wal; Valerie Ehlers (AOSIS, 2004)
A quantitative, descriptive, cross-sectional survey was carried out in the Limpopo Province to identify the perceptions of student nurses, nurse educators and unit supervisors concerning student nurses' clinical accompaniment in this province. Opsomming 'n Kwantitatiewe, beskrywende, deursnitopname is gebruik om die persepsies van verpleegstudente, verpleegopvoedkundiges en eenheidstoesighouers oor verpleegstudente se kliniese begeleiding in the Limpopo Provinsie te identifiseer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.